Dynamics of Acculturation and Enculturation of Languages to Socio-Economic Development in Nigeria: Implication for Poverty Reduction - Abdulrahman, Khadijah Ashiru (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
Every group and society has cultures constituting frameworks for their lives and behavioral patterns. Cultural factors affect socio-economic behavior in at least four ways: its impact on organization and production, attitudes towards consumption and work, the ability to create and manage institutions, and the creation of social networks. Hence, nations' social and economic performance may be viewed through the lens of the cultural factors that contribute to poverty alleviation and improve the livelihoods of its people while recognizing that other factors also contribute to these dynamics. Nigeria is a heterogeneous society renowned for its linguistic diversity and rich cultural heritage, which presents a unique context for examining the influence of language dynamics on socio-economic outcomes. How these processes affect access to education, employment, and economic opportunities, and how they contribute to or hinder poverty alleviation efforts. While evaluating case studies and statistical data, we discovered that the Nigerian multilingual prowess has not been harnessed for the country's socio-economic growth. The study, therefore, highlights the potential of leveraging language policies and educational programs to enhance socio-economic development by deploying descriptive analysis and adopting Functionalism as its framework. We recommend that by embracing linguistic pluralism, policy integration and community empowerment with modern innovations, Nigeria can harness its linguistic diversity and cultural values to drive entrepreneurship, enhance productivity, and promote social cohesion for sustainable socio-economic development.